Multi-resolution based PID controller for frequency regulation of a hybrid power system with multiple interconnected systems - Zhang, Peng; Daraz, Amil; Malik, Suheel Abdullah; Sun, Chao; Basit, Abdul; Zhang, Guoqiang (Frontiers in Energy Research, 2023)
Automatic generation control (AGC) in modern power systems (PS) is difficult because the output power of many power resources is intermittent, and the load and system parameters vary widely. In this paper, a novel control scheme known as the wavelet based multiresolution proportional integral derivative (MRPID) controller for multiple interconnected hybrid power sources is presented. The discrete wavelet transform (DWT) is used in the proposed wavelet based MRPID controller to split the error between the actual and target responses into different frequency components at several stages. To ensure optimum system performance, the gains of the MRPID controller are fine-tuned using the Fox Optimizer Algorithm (FOA), a new powerful metaheuristic technique. The proposed MRPID controller is evaluated in a three-area hybrid system where each area contains a combination of conventional generation (gas, thermal reheat, and hydro) and renewable generation sources (solar, and wind). The proposed controller also accounts for system nonlinearities, including boiler dynamics, time delay, dead band, generation rate limitation, system uncertainties, and load changes. In the hybrid system studied, the proposed MRPID is compared with FOA-tuned PID and PI controllers. The simulation outcomes show that the presented controller outperforms the other control strategies in respect of settling and rise times, undershoot, and overshoot values, and ITSE in the dynamic response of the system. The sensitivity analysis results show that the proposed FOA-MRPID control method is extremely reliable and can efficiently stabilize the load frequency and interconnection line in a multi-area network IPS.